A mixed method for evaluating input devices with older persons - Mahmud, Murni (2006)
This research is an exploratory study which introduces a mixed method in evaluating common input devices. The method includes both quantitative and qualitative approaches and considers both subjective and objective measures. The study incorporates psychometric test to measure user ability, introduces real tasks in the evaluation, and interviews users to elicit their opinions regarding the importance qualities of preferred devices. A mouse, a tablet-with-stylus and a touch screen have been evaluated in two tasks; browsing a website and playing a card game. Thia paper shows the mixed method has made possible a more nuanced understanding of the use of input devices by older persons.